The use of TikTok Functionality by Radio and Television Stations in Poland - Sosnowska, Joanna; Wójciszyn-Wasil, Aneta (Roczniki Kulturoznawcze, 2025)
Social media has significant potential to enhance brand recognition and foster a positive brand image. Traditional media have also begun to recognise this opportunity and create their own profiles on popular communication apps. The aim of this research is to examine how television and radio stations in Poland use the functionalities of the TikTok app to create content. The research material comprises publications from the official TikTok channels of the most popular radio and television stations in Poland. Two categories of traditional media were selected based on the programme profile criterion: news and current affairs (TOK FM, PR24, TVN 24, Polsat News) and universal entertainment (RMF FM, Radio Zet, TVP, POLSAT). The analyses of content and forms of media communication initiate an important discussion in the current research area related to the transformation of traditional media and the dynamically developing TikTok application. The research focuses on the scope of TikTok’s functionality in relation to the characteristics of the medium, station promotion, and building a community around the brand that is a radio and television station.